The Emerging Role of miRNAs and Their Clinical Implication in Biliary Tract Cancer - Nina Nayara Ferreira Martins; Kelly Cristina da Silva Oliveira; Amanda Braga Bona; Marília de Arruda Cardoso Smith; Geraldo Ishak; Paulo Pimentel Assumpção; Rommel Rodríguez Burbano; Danielle Queiroz Calcagno (Gastroenterology Research and Practice)
Biliary tract cancers are aggressive malignancies that include gallbladder cancer and tumors of intra- and extrahepatic ducts and have a poor prognosis. Surgical resection remains the main curative therapy. Nevertheless, numerous patients experience recurrence even after radical surgery. This scenario drives the research to identify biliary tract cancer biomarkers despite the limited progress that has been made. Recently, a large number of studies have demonstrated that deregulated expression of microRNAs is closely associated with cancer development and progression. In this review, we highlight the role and importance of microRNAs in biliary tract cancers with an emphasis on utilizing circulating microRNAs as potential biomarkers. Additionally, we report several single-nucleotide polymorphisms in microRNA genes that are associated with the susceptibility of biliary tract tumors.